The Impact of Leadership Conflict on the Growth and Unity of Church Congregations: A Literature Review by Lewis A. Cosert, Daniel Goleman, Stephen P. Robbins, and Ralf Dahrendorf - Absalina Lusia Lesnussa (Journal of Social Research, 2026)
Leadership conflict is a frequent phenomenon within church organizations and has a significant impact on congregational growth and the unity of the body of Christ. This article analyzes the impact of such conflict by using the perspectives of four scholars: Stephen P. Robbins, through organizational behavior theory and conflict management; Daniel Goleman, through the concept of emotional intelligence in leadership; Lewis A. Coser, through the positive function of social conflict; and Ralf Dahrendorf, through authority-based conflict theory. Using a literature review approach and qualitative analysis, this article finds that poorly managed leadership conflict can lead to a decline in congregational growth, both numerically and spiritually, and can create division within church unity. However, when managed constructively through emotional intelligence and a functional approach, conflict can serve as a catalyst for renewal, stronger relationships, and increased congregational solidarity. The conclusions of this study confirm that leadership conflicts have a dual impact on the growth and unity of the church congregation, where Robbins and Dahrendorf's perspectives point to the inherent and structural nature of conflict, while Goleman and Coser offer practical constructive solutions. Church leaders need to develop high emotional intelligence, implement systematic conflict management, and view conflict as an opportunity for spiritual renewal. With a holistic approach that combines an awareness of power dynamics, emotion management, and negotiation skills, leadership conflicts can be transformed from a threat of division to a constructive force for the growth and unity of the congregation.